English Language Assessment Tools in The Modular Distance Learning: Maintaining Academic Integrity and Validating Student Outcomes - Visto, James; Zaluaga, Zocorro Anne R.; Bucar, Jimmy D. (Future Science / FSH-PH Publications, 2024)
The experiences of English teachers in learning assessment in the modular distance learning modality provide valuable insights into the assessment trends and interventions needed to improve student learning. This study delved into the experiences of English teachers in learning assessment in the modular distance learning modality as a precursor to understanding the assessment trends and interventions in the Department of Education, Division of Bohol, and Tagbilaran City for the school year 2021–2022. A narrative research design was used to understand the experiences of ten (10) purposely selected English teachers from public schools in Bohol and Tagbilaran City Divisions in English assessment in the modular distance learning modality. Semi-structured interviews were conducted to collect data, which was then analyzed using thematic analysis. Results revealed that the selected English teachers in Bohol have been using various assessment tools, methods, and feedback mechanisms during the implementation of modular distance learning. These include diagnostic, formative, and summative assessments and traditional and alternative assessment methods. Teachers have also used multiple feedback mechanisms, including written, online, in-person, and multimodal feedback. To maintain academic integrity, teachers have been providing clear guidance and support to students, avoiding bias and favoritism, and using specific criteria for evaluation. The study also found that teachers have faced challenges in ensuring academic integrity, overcoming logistical and communication barriers, and adapting to new instructional and assessment methods. However, they have demonstrated resilience by aligning their assessment tools with the Most Essential Learning Competencies (MELC), utilizing innovative feedback mechanisms, and promoting academic integrity. The study concludes by recommending that teachers adopt a flexible approach to assessment, promote the alignment of assessment tools with the MELC, encourage multiple feedback mechanisms, promote academic integrity, and provide support and resources to teachers.